Housing and health – a public health perspective. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to provide a viewpoint on homelessness and health gained from a practical public health perspective.Design/methodology/approach – Views derived from local review as well as other national epidemiology and research.Findings – That housing has real impacts upon health especially for those who are homeless.Research limitations/implications – This is a viewpoint from a major city in England.Practical implications – Homelessness leads to extreme vulnerability. There are other aspects of the home environment that impact elsewhere in the public sector, especially the health service. Vulnerable individuals are more likely to become homeless which can lead to exacerbation of vulnerability.Originality/value – This is a viewpoint derived solely from local practice.